Increasing the Children’s Nationalism of Indonesian Migrant Workers (PMI) through Pancasila, Tourism, Culture, and Indonesian Folk Songs in Malaysia - Maharani Harinto Putri; Siti Nur Azizah; Muhammad Juliansyah Akbar; Evelyn Zaalfa Winni Kusuma; Puteri Aprilianeu Cahya Rumara; Silvia Asri Utami (Universitas Muhammadiyah Purwokerto, 2024)
Nationalism is also an awareness of the existence of a country or a spirit of unity within the nation. Also, nationalism affirms Indonesia's diverse identity in various aspects of its culture, so this nationalism is critical. However, most of the children of Indonesian Migrant Workers (PMI) in Malaysia experience an identity crisis due to the children's lack of knowledge about culture and all aspects of Indonesia. Activities are carried out to instill Pancasila values, culture, historical tourism, and Indonesian folk songs to increase nationalism and love for the Indonesian homeland. The learning method for introducing folk songs begins with bridging, giving examples, and singing together lively. After carrying out the activities, children became more aware of the values of nationalism and more appreciative of cultural, religious, and ethnic differences, and they were able to maintain harmony between citizens. This activity needs to be continued with a more innovative and creative delivery method to children to achieve the goal that PMI children in Malaysia can have a solid national identity.